PSYCHIATRIC URGENCY AND EMERGENCY CARE NURSES: AN ANALYSIS OF THEIR PROFESSIONAL AND EDUCATIONAL PROFILE - Divane de Vargas; Janaina Soares; Talita Dutra Ponce; Bruna Batista de Oliveira (Universidade Federal do Paraná, 2017)
The present study characterized the professional and educational profile of nurses working at psychiatric urgency and emergency services, identifying its association with clinical practice. A cross-sectional study was carried out with 184 nurses in 17 psychiatric urgency and emergency healthcare services in the state of São Paulo from February to October 2012. A significant association was found between the profile of nurses and clinical practice in psychiatric urgency and emergency care, and the greatest predictors of this association were: male gender (OR=9.05), length of time in the profession longer than 10 years (OR=2.67), and having graduated at public educational institutions (OR=2.14). The prevalence of male nurses in psychiatric urgency and emergency care services suggests the perpetuation of the model based on physical strength. Professional experience and increased workload during undergraduate studies are factors that may lead to a better clinical practice in psychiatric emergency services